Is project-based transdisciplinary assessment effective in reducing the Mathematical anxiety of pre-service Biology teacher? - Jessica Elfani Bermuli; Kimura Patar Tamba (Universitas Negeri Jakarta, 2021)
Mathematical anxiety is a constant obstacle experienced by pre-service Biology Teachers in developing their quantitative abilities. Project-based transdisciplinary assessment is one type of transdisciplinary application that has not been widely explored to solve this problem. Project-based transdisciplinary assessment in form of mini-research with the topic “Data Collection on local wisdom in each area”. The aim of this study is to determine the impact of implementing project-based transdisciplinary assessment on reducing mathematics anxiety among 23 pre-service biology Teachers. This study used a pre-experimental method with a pre-test and post-test design with one non-randomized group. The pre-test and post-test were carried out using the AMAS (Abbreviated Math Anxiety Scale) questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon signed ranks test. Statistical results of this study show no significant difference in mathematics anxiety before and after the implementation of the project-based transdisciplinary assessment with a z value of-0.163 and a p-value of 0.87. Based on the aspect of mathematics anxiety, there is also no significant difference in mathematics learning anxiety and mathematics evaluation anxiety when compared before and after the implementation of project-based transdisciplinary assessment with each z value = -0.664, p = 0.506 and z = -0.931 and p = 0.352. The implication of this research is the need for a continuous, collaborative and institutional effort in the transdisciplinary application so as to improve the quantitative abilities of pre-service Biology Teachers.